Factors Affecting Mortality in People Living with HIV with Antiretroviral Therapy: A Meta-Analysis - Fauziah Shinta Anindita; Fenita Indriani; Bhisma Murti; Nindita Arum Veibiani (Masters Program in Public Health, 2024)
Background: TB is the leading cause of death among people living with HIV. In 2020, an estimated 214,000 people living with HIV died from TB. People with AIDS have a severely damaged immune system. They are increasingly suffering from severe diseases, called opportunistic infections (OI). This study aims to analyze and estimate the influence of gender, TB Coinfection, Opportunistic Infection on mortality in ODHIV with Antiretroviral Therapy.Subjects and Method: Systematic review and meta-analysis using PRISMA flowchart and the PICO model. Population: ODHIV with ART. Intervention: Women, Co-infected TB, Opportunistic Infections. Comparison: Male, no co-infected TB, no Opportunistic Infection. Outcome: Mortality Article search using Google Scholar, PubMed and Science Direct databases. The keywods used include